2017
DOI: 10.1007/s11136-017-1761-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life changes after primary septorhinoplasty

Abstract: Septorhinoplasty can improve disease-specific and non-disease-specific QOL in the short- and long-term postoperative period. These improvements remain measurable 5 years after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
4
22
1
2
Order By: Relevance
“…Although not significant, the patients in the advanced stage SR group performed worse (ROE score only 54.2). The findings of the whole PR or SR group were similar to ROE scores following conventional rhinoplasty measured previously in our institution (1-year ROE score 68.5, 5-year ROI score 75.1) (16,17) . Although we did not observe statistically significant differences between the groups, it is interesting to note that the ROE scores of PR patients clustered in the very high range and that the aesthetic perception for advanced stage SR patients is reduced.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although not significant, the patients in the advanced stage SR group performed worse (ROE score only 54.2). The findings of the whole PR or SR group were similar to ROE scores following conventional rhinoplasty measured previously in our institution (1-year ROE score 68.5, 5-year ROI score 75.1) (16,17) . Although we did not observe statistically significant differences between the groups, it is interesting to note that the ROE scores of PR patients clustered in the very high range and that the aesthetic perception for advanced stage SR patients is reduced.…”
Section: Discussionsupporting
confidence: 86%
“…Low-level scores can most likely be attributed to revision rhinoplasty operations or different mean follow-up periods (between 5 and 60 months) (16) . The mean follow-up period of PR and SR groups was 2.4 years in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is intended to be a general assessment, as it also takes into account optical and functional data. The analysis of functional results revealed a significant change in the patientsʼ perception of nasal function 12 and 60 months postoperatively [138]. Furthermore, the authors confirmed that patients with a preoperative crooked nose were significantly more satisfied after surgery than patients with a straight preoperative nose.…”
Section: Quality Of the External And/or Cosmetic Results And The Qualmentioning
confidence: 70%
“…In one of the largest follow-up papers (60 months), Bulut and Baumann et al confirmed that the ROE after one and after five years showed significant postoperative improvement in the outer appearance and quality of life [138]. This is the only study that evaluated this long follow-up period for the field of septorhinoplasty.…”
Section: Quality Of the External And/or Cosmetic Results And The Qualmentioning
confidence: 89%
“…Neben den klassischen Endpunkten Morbidität und Mortalität und anderen, arztbasierten Ergebnisparametern hat das PRO in den letzten Jahren bei der Bewertung der Ergebnisqualität eine deutliche Aufwertung erfahren, weil man -insbesondere mit der Lebensqualität -messen kann, "was beim Patienten ankommt" (am Beispiel Rhinoplastik: [19,20]).…”
Section: Pro Und Lebensqualitätunclassified